Design, construction and commissioning of a laboratory type drum type magnetic concentrator - Forero-Pinilla, Álvaro; Alarcón-Sichacá, Héctor Hely; Acosta-Hernández, Yesid Rolando (Universidad Pedagógica y Tecnológica de Colombia, 2010)
The purpose of this project is to design and build a magnetic separation equipment, starting from the selection of the prototype to establishing the foundations of the previously established design. The main criteria that must be taken into account to be incorporated in any design and construction of a magnetic concentrator are identified and analyzed.